A Study Of Factors Affecting The Cosumption Of Middle East Cuisines In Klang Valley - Siti Irwani, Binti Ismail (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study is carried out to determine the factors affecting the consumption of MiddleEast cuisines in Klang Valley. Preliminary observation had been done in major areas such as Seremban, Bukit Bintang, Ampang, Kampung Pandan, and Shah Alam and it is shown that there are emerging numbers of Middle-East restaurant in line with the increased demand by the number of diversified customers flocking to the restaurants. This may due to the overseas cuisines and cultural experiences when travelling or outstation and also widely exposures and coverage by the media, which have made the people “adventurous in trying new cuisines” (Kavita et al., 2011). The factors affecting the consumption are determined in this study. Theory of Planned Behavior is used to discover the variables in this study. This is a quantitative study in which numerical data are obtained from self-administered survey questionnaire. The sample of this study is the customer available in the Middle-East restaurants in Klang Valley and workers in various governments and private organizations located in Klang Valley. There are 400 sets of questionnaire are distributed. The data collected is analyzed by using descriptive statistic, correlation analysis and regression analysis. The findings of this study justified that all of the hypotheses proposed earlier on are accepted.